The impact of ESG management on investment decision: Institutional investors' perceptions of country-specific ESG criteria - So Ra Park; Jae Young Jang (International Journal of Financial Studies, 2021)
Existing global ESG models are limited in terms of applicability and predictability, especially in countries with an unstable environment. On the other hand, utilizing internally made or privately sourced ESG models have caused issues relating to generalizability, comparability, and continuity. In our research, we present an ESG framework that is specific to South Korea, which has both global and country-specific factors in all three categories. The AHP model is used to determine how the three categories' materiality would be viewed by institutional investors as well as how country-specific factors rank against global factors. The results of this study show that institutional investors place more importance on environmental and governance factors compared to social factors. Factors including shareholders' rights, pollution and waste, greenhouse gas emissions, and risk and opportunity management are found to have greater influences on investors' investment decisions. In addition, it was confirmed that both of the country-specific variables for South Korea, partnership with subcontractor and CEO reputation, have a significant influence on investment decisions. By having the ESG model validated by institutional investors, who are the main users of ESG disclosures of corporations, our methodology of presenting a country-specific model can be benchmarked by studies on other emerging markets with a variety of country-level specificities.
Keywords: 330; analytical hierarchy process (AHP); CEO reputation; ESG investment; ESG management; institutional investor; Korean specific ESG model; partnership with subcontractor